2022
DOI: 10.11591/ijere.v11i1.21969
|View full text |Cite
|
Sign up to set email alerts
|

Engineering students’ judgments on the favorable effect that the class context has on their academic learning

Abstract: <p><span>The COVID-19 pandemic has impacted human life, including educational settings. In Mexico, teachers and students found it necessary to adopt the online modality at all levels. As a result, both students and teachers face new demands and a re-conceptualization of their everyday academic lives. This study explored the engineering students' perception of the favorable effect level that the class context has on their learning. There were 551 participants took a cognitive algebra study. The expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Consistent with the above, observed that university students enrolled in a psychology course presented changes in the content specialization of their knowledge networks; the conceptual nodes tended to be more specific and closely related to the subject studied. On the other hand, Morales-Martinez et al (2022) reported that the quality of mathematical concepts retrieved by engineering students differed according to their level of academic performance. Students with lower grades retrieved more general knowledge concepts on the subject.…”
Section: Constructive Cognitive Evaluationmentioning
confidence: 99%
“…Consistent with the above, observed that university students enrolled in a psychology course presented changes in the content specialization of their knowledge networks; the conceptual nodes tended to be more specific and closely related to the subject studied. On the other hand, Morales-Martinez et al (2022) reported that the quality of mathematical concepts retrieved by engineering students differed according to their level of academic performance. Students with lower grades retrieved more general knowledge concepts on the subject.…”
Section: Constructive Cognitive Evaluationmentioning
confidence: 99%
“…Meningkatkan motivasi belajar, dapat dilakukan dengan cara pandang siswa di dalam kelas, maksudnya siswa mampu membaca situasi kelas selama pembelajaran dan mengembangkan kemampuannya dalam belajar. Cara siswa memandang kelas dan pengaruhnya terhadap pembelajaran sangat mempengaruhi motivasi siswa untuk bertahan dan mencapai tujuan akademik mereka [7]. Keberhasilan suatu tujuan pendidikan tergantung pada bagaimana proses di dalam kelas [8].…”
Section: Pendahuluanunclassified